Integrasi Nilai-Nilai Ayat Al-Quran Melalui Budaya Lokal Kepercayaan Masyarakat Terhadap Tradisi Pawang Hujan Perspektif Maqashid Al-Syari’ah - Ramadhan, Aditya (Jurnal Dinamika Sosial Budaya, 2023)
Culture and humans can be seen as inseparable because both shape life.    The purpose of this study is to understand the extent to which the tradition of rain handlers in community beliefs can be intervened through the integration of values in the verses of the Qur'an and reviewed through the maqashid sharia point of view. The research method used is qualitative with a case study approach, involving 138 respondents selected using a purposive sampling technique. The main instrument used was a questionnaire, and data collection was conducted in compliance with research ethics. Data analysis was conducted through content analysis techniques. In Indonesia, culture is defined as different behaviors that are passed down through generations. In terms of cultural misconceptions, Indonesia has diverse cultural qualities, such as the culture of rain handling. This is common during major events, and rain handlers are instructed to shift the wind and clouds. And in its operation it still causes controversy. The concept of maqashid sharia does not influence the legal basis of the rain handler tradition. The rain guide tradition is based on mutual benefit and maslahat mursalah. The practice of the rain guide tradition can also be inspired by the munasabah verse of the Qur'an, so that the rain guide tradition still has a position in its implementation, and the local culture of the rain guide tradition includes aspects of living habits that involve the scope of sociology and cultural anthropology